ASPECTOS BIOLÓGICOS, COMPORTAMENTO DE CÓPULA E SENSILAS ANTENAIS DE BOTHYNUS STRIATELLUS (COLEOPTERA: SCARABAEIDAE: DYNASTINAE) - MARTINS, Gabriella Torres; RODRIGUES, Sérgio Roberto (ANAIS DO ENIC, 2023)
-